"I am stuck in meetings": Understanding the relation of CEO time management with TMT size and gender diversity. Issue 5 (October 2020) - Rovelli, Paola
Abstract: Time is a scarce resource, especially at the apex of firms. CEOs' time management became a hot topic in recent academic and practice-oriented literature, which stressed the fact that CEOs are usually stuck in meetings. In this paper, I advance the nascent literature on the CEOs' time management by focusing on the time the CEOs spend in meetings and on their choice of scheduling group meetings instead of bilateral meetings. Doing so, I study the relation of the CEOs' time management with their top management team's (TMT's) size and gender diversity. Empirical analyses over a sample of 170 CEOs revealed a positive and significant relation between the size of the TMT and the time the CEOs spend in meetings with the top executives belonging to the TMT, while no significant relation emerged between the TMT's gender diversity and the CEOs' time in meetings. Conversely, while the TMT's size does not significantly relate to the amount of time the CEOs spend in group meetings, a U-shaped relation emerged with the TMT's gender diversity: the time spent in group meetings is higher when the TMT is homogeneous in gender, while CEOs prefer bilateral meetings when the TMT is heterogeneous.